PARADOKS ORGANISASIONAL: DILEMA MANAJERIAL DALAM PEMILIHAN ALOKASI SUMBER DAYA ORGANISASI (STUDI KASUS ADMINISTRASI PUBLIK PENDIDIKAN TINGGI - Soemanagara, Rizky Dermawan (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2008)
Resource allocation resolution is essential for achieving organizational goals. It is related to inter-actor social interaction, in the form of position bargaining. In this case, analysis on educational policy should be based upon the main framework that education is public goods. When education is so-called public goods, all decisions on educational policy are thought to be within political domain. Thus, its administration becomes politically bound public administration. This research applies organizational analysis. The writer chose this tool analysis by reason of the fact that all activities to accomplish vision and missions carried out by social actors are within organizational span. Balancing organizational paradox can be attained by linking it to organizational vision, through system and organization structure approaches. The system of higher education is believed to be loosely coupled system. One thing to be noted is that the education system does not tightly bind higher education institutions. There is no consensus between universities and education system.There is no tight internal bound within organization, but one goal commitment, i.e. educational performance.